Law Enforcement Against the Criminal Act of Online Gambling in the Jurisdiction of Central Aceh - Indah Permata Sari; Fitri Rafianti; T. Riza Zarzani (PT. Sinergi Legal Publisher, 2025)
The phenomenon of online gambling has become a form of cybercrime that is increasingly prevalent in various regions, including in special autonomous regions such as Central Aceh. This article critically examines law enforcement against online gambling crimes using normative and juridical-empirical approaches, particularly in the context of the application of national law and Aceh Qanun Number 6 of 2014 concerning Jinayat Law. The study results indicate that law enforcement still faces various substantial and structural obstacles, such as regulatory disharmony between national criminal law and Jinayat law, limited technical capacity of law enforcement officers in handling digital crimes, and low public legal awareness of the prohibition of gambling crimes. Although Aceh has local legal instruments based on Islamic law, their implementation has not been fully effective in addressing the dynamics of technology-based crime. The author recommends the need for harmonization of legal norms, strengthening digital forensic institutions, and an educational approach based on local values ​​to realize an adaptive and equitable law enforcement system in the Aceh region.